2015
DOI: 10.1111/eje.12147
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging intrinsic motivation in the clinical setting: teachers' perspectives from the self‐determination theory

Abstract: Our findings regarding dental education expand on the research outcomes from other health professions about how teachers may support students to internalise behaviours. An autonomy-supportive environment may lead students to value and engage in academic activities and eventually foster the use of an autonomy-supportive style to motivate their patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 42 publications
0
48
0
2
Order By: Relevance
“…The final aim should be to create a learning climate that fosters the conditions for students to become self-motivated rather than trying to control their behaviour. 19,36,37 On the other hand, feedback, which is an external input, should be given in a way that supports students' needs so it is accepted and internalised and serves as a nutrient for students' autonomous moti- be based on empathy and assertiveness. 9,19 In this investigation, we have focused on the predictive value of the learning climate and the quantity and quality of feedback; however, there is abundant room for future research to test other variables that may favourably influence dental students' needs and autonomous motivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The final aim should be to create a learning climate that fosters the conditions for students to become self-motivated rather than trying to control their behaviour. 19,36,37 On the other hand, feedback, which is an external input, should be given in a way that supports students' needs so it is accepted and internalised and serves as a nutrient for students' autonomous moti- be based on empathy and assertiveness. 9,19 In this investigation, we have focused on the predictive value of the learning climate and the quantity and quality of feedback; however, there is abundant room for future research to test other variables that may favourably influence dental students' needs and autonomous motivation.…”
Section: Discussionmentioning
confidence: 99%
“…18 The need for relatedness means being accepted and valued; it is a feeling of belongingness or connectedness with others as well as with a significant community, eg teachers, fellow students or patients. 16 Despite the importance placed by dental educators on the satisfaction of students' basic psychological needs, 19 a recent systematic review revealed that no study so far had tested the mediating role of these needs between different social factors and dental students' motivation and that little attention has been paid to which variables influence students' motivation. 20 Therefore, the purpose of this study was to test the mediating role of basic psychological needs on the relation between learning climate and feedback and dental students' motivation.…”
Section: Introductionmentioning
confidence: 99%
“…This individual is motivated by enjoyment, satisfaction and an inherent interest in the activity. 19 Orsini and colleagues 36 have also identified the importance of an autonomy-supportive approach in clinical teaching with benefits for professional practice. The authors explained that this technique represents a 'human-centered' approach to teaching, which equips students with the skills to offer autonomy-support to patients, thus improving healthcare delivery.…”
Section: A J P E a C C E P T E D D R A F Tmentioning
confidence: 99%
“…The majority are extremely motivated (Nuffer et al, 2017;Khalil et al, 2018), and believe that they need a college education to achieve their career goals (Ottenberg et al, 2016;Worly et al, 2018). These individuals consider all aspects of life from a global perspective (Fryer et al, 2016;Berger et al, 2019), tend to adopt technology at its highest levels (Hennessy et al, 2016;Shatto and Erwin, 2017), expect on-demand services (Orsini et al, 2016b) that are always available (Woolley and Fishbach, 2018;Manspeaker et al, 2019) and easily accessible (Fond et al, 2018;Lysak et al, 2018). Hence, they prefer educational opportunities that allow them to stay connected with technology (Agius et al, 2018), and expect their educators to do the same (Joshi et al, 2017;Mor et al, 2018).…”
Section: Generational Characteristics Of Present-day Health Care Profmentioning
confidence: 99%
“…In addition, millennial students often feel that they are not provided with enough justifications for the learning activities that are expected of them (Brass et al, 2017;Manzi et al, 2017;Mabel and Britton, 2018), or sufficient explanations of how these activities align with the overall academic goals (Tai et al, 2016;Chen et al, 2017). This is in marked contrast to the mind-set of educators from earlier generations who expect their students to unquestioningly follow instructions (Orsini et al, 2016b;de Paiva et al, 2017). This can lead to feelings of apprehension (Wilkinson et al, 2014;Bhagat et al, 2015) and distrust (Rogers and Tutty, 2016;Persky and McLaughlin, 2017) in the learning environment.…”
Section: Challenges Of Present-day Health Care Educationmentioning
confidence: 99%